Prevalence of Salmonella enterica Subspecies enterica Serovar Typhi (Salmonella typhi) Infection in Febrile Patients at the Sino-Gabonese Friendship Hospital in Franceville: A Two-Year Retrospective Study in South East Gabon - Thiéry Ndong Mba1, 2*; Hilaire Moundounga Kenguele1; Ulrick Nzamba3; Arnaud Brice Pambo-Pambo4; Romial Zang Mintsa3; Patrick Mickala1, 4 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Salmonella enterica subspecies enterica serovar Typhi (Salmonella typhi) causes typhoid fever. This disease is a global public health problem, particularly in developing countries like Gabon. Unfortunately, to our knowledge, little information exists in the epidemiological literature on the prevalence of Salmonella enterica infection in patients presenting with febrile illness in Gabon, particularly at the Sino-Gabonese Friendship Hospital in Franceville, in the southeast of the country. Methods: A retrospective, crosssectional study was conducted using the "Widal and Felix" serodiagnostic test results of febrile patients archived in the Medical Analysis Laboratory Records of the Sino-Gabonese Friendship Hospital in Franceville from June 2019 to May 2021. Results: The prevalence of Salmonella typhi in febrile patients was 58.88% [95% CI: 0.5 - 0.6]. The participants' age ranged from 15 to 49 years (mean 24.79 years). We observed that with 1724 cases and a percentage of 62.15% (P < 0.001), women were more infected than men, and the most affected age group was 14 to 49 years, with 1379 cases (49.71%). During the study period, the seasonal distribution of Salmonella typhi infection indicated that quarter 6, corresponding to the small rainy season, with 16.58%, i.e., 460 cases, had the highest cases. Conclusion: These results highlight the need to strengthen food safety hygiene in community markets and environmental sanitation to break the Salmonella typhi transmission in Franceville, Southeast Gabon.